Biosocial and disease conditions are associated with good quality of life among older adults in rural eastern Nepal: Findings from a cross-sectional study - Yadav, Uday Narayan (PLoS One, 2020)
BACKGROUND: The ageing population in most low-and middle-income countries is accompanied by an increased risk of non-communicable diseases culminating in a poor quality of life (QOL). However, the factors accelerating this poor QOL have not been fully examined in Nepal. Therefore, this study examined the factors associated with the QOL of older adults residing in the rural setting of Nepal. METHODS: Data from a previous cross-sectional study conducted among older adults between January and April 2018 in in rural Nepal was used in this study. The analytical sample included 794 older adults aged ≥60 years, selected by a multi-stage cluster sampling approach. QOL was measured using the Older People’s Quality of Life tool; dichotomized as poor and good QOL. Other measures used included age, gender, ethnicity, religion, marital status, physical activity, and chronic diseases such as osteoarthritis, cardiovascular disease, diabetes, chronic obstructive pulmonary disease (COPD), and depression. The factors associated with QOL were examined using mixed-effects logistic regression. RESULTS: Seven in ten respondents (70.4%) reported a poor QOL. At the bivariate level, increasing age, unemployment, intake of alcohol, lack of physical activity as well as osteoarthritis, COPD and depression were significantly associated with a lower likelihood of a good QOL. The adjusted model showed that older age (AOR = 0.50, 95% CI: 0.28–0.90), the Christian religion (AOR = 0.38, 95% CI: 0.20–0.70), and of an Indigenous (AOR: 0.25; 95% CI: 0.14–0.47), Dalit (AOR: 0.23; 95% CI: 0.10–0.56), and Madheshi (AOR: 0.29; 95% CI: 0.14–0.60) ethnic background were associated with lower odds of good QOL. However, higher income of >NRs 10,000 (AOR = 3.34, 95% CI: 1.43–3.99), daily physical activity (AOR: 3.33; 95% CI: 2.55–4.34), and the absence of osteoarthritis (AOR: 1.9; 95% CI: 1.09–3.49) and depression (AOR: 3.34; 95% CI: 2.14–5.22) were associated with higher odds of good QOL. CONCLUSION: The findings of this study reinforce the need of improving QOL of older adults through implementing programs aimed at addressing the identified biosocial and disease conditions that catalyse poor QOL in this older population residing in rural parts of Nepal.